2016
DOI: 10.1177/0886260516642294
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate Rumination and Positive Reappraisal as Serial Mediators Between Life Impact and Posttraumatic Growth in Victims of State Terrorism in Chile (1973-1990)

Abstract: This study examines the role of coping strategies related to positive reappraisal versus other cognitive strategies (deliberate rumination) as mediators between life impact and posttraumatic growth in survivors of the military dictatorship in Chile between 1973 and 1990 (tortured political prisoners and family members of political prisoners executed and missing). Survey data from 251 political violence survivors were analyzed using the SPSS PROCESS macro for bootstrapping indirect effects (Hayes, 2013). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…It is an active cognitive process that involves reconstructing an existing schema to promote PTG. The effects of deliberate rumination on PTG have been demonstrated in the literature (Tedeschi and Calhoun, 2004, Calhoun and Tedeschi, 2006), and higher levels of deliberate rumination have been found to be associated with greater PTG (Linley and Joseph, 2004; Taku et al, 2008; Triplett et al, 2012; Zhou and Wu, 2015; Cárdenas et al, 2019). In particular, Triplett et al (2012) found that deliberate rumination mediates the relationship between intrusive rumination and PTG.…”
Section: Introductionmentioning
confidence: 90%
“…It is an active cognitive process that involves reconstructing an existing schema to promote PTG. The effects of deliberate rumination on PTG have been demonstrated in the literature (Tedeschi and Calhoun, 2004, Calhoun and Tedeschi, 2006), and higher levels of deliberate rumination have been found to be associated with greater PTG (Linley and Joseph, 2004; Taku et al, 2008; Triplett et al, 2012; Zhou and Wu, 2015; Cárdenas et al, 2019). In particular, Triplett et al (2012) found that deliberate rumination mediates the relationship between intrusive rumination and PTG.…”
Section: Introductionmentioning
confidence: 90%
“…similarly Cox and McAdams, 2014;Merrill et al, 2016;Holm and Thomsen, 2018;Lilgendahl and McLean, 2020). In the same vein, another study found that victims of the Chilean dictatorship who intentionally reflected on their experience only showed post-traumatic growth if they also reframed it positively (Cárdenas Castro et al, 2019).…”
Section: Autobiographical Reasoningmentioning
confidence: 90%
“…Also, IMs have rarely been studied outside the context of psychotherapy sessions. However, we expect IMs to be identifiable also in elicited narratives of autobiographical memories, because narratives are about events that happened out-of-the-ordinary, that breach canonical expectations (Bruner, 1990). With regard to habitual rumination versus reflection, we expect reflectors to use more IMs than ruminators, based on the idea that IMs indicate a more flexible thinking style.…”
Section: The Present Studymentioning
confidence: 99%
“…The life impact of the violence affects subjects’ basic beliefs about themselves, others, and the world (Janoff-Bulman, 2006). These experiences must be systematically reviewed (Taku et al, 2007; Triplett, Tedeschi, Cann, Calhoun, & Reeve, 2012) and positively reappraised (Cárdenas, Arnoso, & Faúndez, 2016) to reconstruct anew their basic beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…This process would involve an effort to adapt to unfavorable circumstances by attempting to construct a new narrative about who we are, about others, and about the place where the interaction with others takes place (Cárdenas et al, 2016; Tuval-Mashiach et al, 2004). Posttraumatic growth promotes changes in three areas: (a) in the self, by improving self-image and increasing self-confidence to cope with adversities; (b) relationship with others, by strengthening relationships, allowing feelings of compassion and empathy to emerge, along with an increase in social support and helping behaviors; and (c) spirituality and life philosophy, when people reassess what is really important and transcendent after the traumatic experience (Calhoun & Tedeschi, 1999; Tedeschi, Park, & Calhoun, 1998).…”
Section: Introductionmentioning
confidence: 99%